Preoperative Prediction of Difficult Laparoscopic Cholecystectomy using Risk Score for Conversion from Laparoscopic to Open Cholecystectomy: An Observational Study - Acharya, Bishal; Dulal, Saujan; Yadav, Bidhyanand; Aryal, Shishir; Sarraf, Soni Kumari; Subedee, Aadesh; Ghimire, Iswar Chandra; Tamrakar, Kishor Kumar; Neupane, Harish Chandra; Lama Gole, Senjisha (Journal of Institute of Medicine Nepal, 2024)
Introduction Laparoscopic cholecystectomy requires experts for the best result. Occasionally laparoscopic cholecystectomy becomes difficult, requiring conversion to open cholecystectomy and also endangers patients causing potential biliovascular and bowel injury. This study aims to predict difficult laparoscopic cholecystectomy using RSCLO scoring system. Methods A prospective observational study was conducted including 116 diagnosed case of cholelithiasis undergoing elective laparoscopic cholecystectomy from July 2023 to March 2024. Scores were given on history, physical examination and ultrasonographic findings on admission as per the RSCLO scoring system. Intraoperatively, difficult laparoscopic cholecystectomyn criteria included: Time taken >60 min or bile/stone spillage or injury to bile duct/artery or conversion to open surgery. The end point of study was the end of surgery. Results The mean age was 46.23+15.36 years with female predominance of 69%. Preoperatively, 31.9% patients were predicted to have difficult cholecystectomy and intraoperatively 37.1% had difficulty (pearson chi-square 77.096, p value <0.001). Age >50 years, male gender and prior history of hospitalization because of gallbladder pathology were significantly associated with difficult laparoscopic cholecystectomy. There was no open conversion, no intraoperative biliovascular or bowel injury. Sensitivity and specificity of RSCLO score with cut off value of >6 was 94.6% and 90%, respectively, with AUROC 0.922. Conclusion RSCLO scoring system is useful for prediction of difficult laparoscopic cholecystectomy and patients with high risk can be counseled preoperatively about intraoperative difficulty.